PERAN KEWIRAUSAHAAN SOSIAL DALAM PENGEMBANGAN SUSU ETAWA PLUS HERBAL SEBAGAI STRATEGI PEMBERDAYAAN EKONOMI MASYARAKAT - Su'amah, Su'amah (Visi Pencerah Nusantara, 2025)
The purpose of this study is to see how social entrepreneurship functions as a strategy for community economic empowerment when developing the Susu Etawa Plus Herbal product. This study reveals how a social entrepreneurship approach can increase value-added products, increase income, and create jobs by utilizing the local potential of Etawa milk and herbal-based innovations. Data were obtained through observation, in-depth interviews, and document analysis through qualitative methods with case studies in Etawa milk producing areas. The results of the study show that product innovation, collaboration with local communities, and sustainable business models contribute greatly to strengthening the community's economy. Social entrepreneurship also helps improve skills, strengthen community solidarity, and improve environmental sustainability. The results show that in supporting economic empowerment and creating sustainable social impacts, a local potential-based approach and product innovation are very important.